Prevalence, Vascular Distribution, and Multiterritorial Extent of Subclinical Atherosclerosis in a Middle-Aged Cohort: The PESA (Progression of Early Subclinical Atherosclerosis) Study. Issue 24 (16th June 2015) - Fernández-Friera, Leticia; Peñalvo, José L.; Fernández-Ortiz, Antonio; Ibañez, Borja; López-Melgar, Beatriz; Laclaustra, Martín; Oliva, Belén; Mocoroa, Agustín; Mendiguren, José; Martínez de Vega, Vicente; García, Laura; Molina, Jesús; et al.
Abstract : Background—: Data are limited on the presence, distribution, and extent of subclinical atherosclerosis in middle-aged populations. Methods and Results—: The PESA (Progression of Early Subclinical Atherosclerosis) study prospectively enrolled 4184 asymptomatic participants 40 to 54 years of age (mean age, 45.8 years; 63% male) to evaluate the systemic extent of atherosclerosis in the carotid, abdominal aortic, and iliofemoral territories by 2-/3-dimensional ultrasound and coronary artery calcification by computed tomography. The extent of subclinical atherosclerosis, defined as presence of plaque or coronary artery calcification ≥1, was classified as focal (1 site affected), intermediate (2–3 sites), or generalized (4–6 sites) after exploration of each vascular site (right/left carotids, aorta, right/left iliofemorals, and coronary arteries). Subclinical atherosclerosis was present in 63% of participants (71% of men, 48% of women). Intermediate and generalized atherosclerosis was identified in 41%. Plaques were most common in the iliofemorals (44%), followed by the carotids (31%) and aorta (25%), whereas coronary artery calcification was present in 18%. Among participants with low Framingham Heart Study (FHS) 10-year risk, subclinical disease was detected in 58%, with intermediate or generalized disease in 36%. When longer-term risk was assessed (30-year FHS), 83% of participants at high risk had atherosclerosis, with 66% classified as intermediate or generalized. Conclusions—: Subclinical atherosclerosis was highly prevalent in this middle-aged cohort, with nearly half of the participants classified as having intermediate or generalized disease. Most participants at high FHS risk had subclinical disease; however, extensive atherosclerosis was also present in a substantial number of low-risk individuals, suggesting added value of imaging for diagnosis and prevention. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01410318. Abstract : Supplemental Digital Content is available in the text.